2014
DOI: 10.1364/oe.22.032071
|View full text |Cite
|
Sign up to set email alerts
|

Nanofocusing of terahertz wave in a tapered hyperbolic metal waveguide

Abstract: An tapered hyperbolic metal waveguide is suggested for the nanofocusing of terahertz waves. We numerically show that, at the frequency of 1 THz, the focal spot can be as small as only 5 nm, which is smaller than that of a plate waveguide by 2 orders of magnitude. Correspondingly, the longitudinal component of the energy flow density is stronger than that of a plate waveguide by 3 orders of magnitude for the same input. It is shown that these significant improvements come from the small imaginary part of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In judiciously designed plasmonic antennas, local spots of particularly enhanced electric or magnetic field can be formed, referred to as hot spots. The hot spots typically arise from the interaction between adjacent parts of a plasmonic antenna separated by a small gap [2,3] but they can be also based on the lightning rod effect (a concentration of the field at sharp features of the antenna) [4][5][6] or combination of both. In various studies, electric hot spots have been reported over a broad spectral range from THz [5] (hot spot size λ/60000 predicted from electromagnetic simulations, * vlastimil.krapek@ceitec.vutbr.cz with λ denoting the wavelength of the incident wave) to visible [7] (hot spot size λ/600 and enhancement >500).…”
Section: Introductionmentioning
confidence: 99%
“…In judiciously designed plasmonic antennas, local spots of particularly enhanced electric or magnetic field can be formed, referred to as hot spots. The hot spots typically arise from the interaction between adjacent parts of a plasmonic antenna separated by a small gap [2,3] but they can be also based on the lightning rod effect (a concentration of the field at sharp features of the antenna) [4][5][6] or combination of both. In various studies, electric hot spots have been reported over a broad spectral range from THz [5] (hot spot size λ/60000 predicted from electromagnetic simulations, * vlastimil.krapek@ceitec.vutbr.cz with λ denoting the wavelength of the incident wave) to visible [7] (hot spot size λ/600 and enhancement >500).…”
Section: Introductionmentioning
confidence: 99%
“…Also, localizations of incident/transmitted light before/after the gap can be incorporated to increase the field enhancement in the gap [322][323][324][325] (Figure 30). The other example is to make use of hybridization of a gap with plasmonic metastructures or metaelements [71,114,191,[320][321][322][323][324][325][326][327][328][329] that results in intensive localization of electric field in the form of surface waves such as vortexplasmon and spoof surface plasmon modes.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Experimental realization of a coupling based on this idea was reported in a number of papers, see Ref. 42 and references therein.…”
Section: Discussionmentioning
confidence: 99%
“…The most nontrivial outcome of Eqs. (42), (43) and Fig. 10 is that, at frequency close to the surface plasmon frequency ω 0 / √ 2, the ratio of the transfer rates to left and to the right switches abruptly from 0 to 1 depending on the relation between the opening angles.…”
Section: Interaction Of Two Emitters At the Metal-air Surfacementioning
confidence: 95%
See 1 more Smart Citation